2022
DOI: 10.32345/usmyj.4(134).2022.22-28
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changes in the vaginal microbiome and chronic endometritis on the initiation of hyperplastic processes of the endometrium in women

Abstract: the article presents a review of the literature, which examines the impact of changes in the vaginal microbiome and chronic endometritis on the development of hyperplastic processes of the endometrium in women. Many studies have proven the undoubted role of these factors in the development of endometrial hyperplastic processes, such as atypical hyperplasia and endometrial polyposis. Chronic endometritis, on the background of which there was a course of endometrial hyperplasia, in 95.1% of women studied was cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Proliferative changes persist in the endometrium, which, with long-term estrogen stimulation, acquire the character of hyperplasia. Also, endometrial hyperplasia can be the cause of the development of endometrial cancer, which is the most common gynecological malignancy [2,[23][24][25]. In 20-25 % of cases, endometrial hyperplasia with atypia is the basis for the formation of malignant endometrial tumors, therefore, the study of all possible factors influencing the induction of endometrial proliferation is an urgent goal of modern research [5].…”
Section: Results and Their Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Proliferative changes persist in the endometrium, which, with long-term estrogen stimulation, acquire the character of hyperplasia. Also, endometrial hyperplasia can be the cause of the development of endometrial cancer, which is the most common gynecological malignancy [2,[23][24][25]. In 20-25 % of cases, endometrial hyperplasia with atypia is the basis for the formation of malignant endometrial tumors, therefore, the study of all possible factors influencing the induction of endometrial proliferation is an urgent goal of modern research [5].…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…Representatives of the Enterobacteriaceae family (E. coli) and Gram-positive cocci (staphylococci and streptococci) prevailed among the aerobic flora. Patients with endometrial polyps showed the largest spectrum of isolated microorganisms [2,9].…”
Section: Results and Their Discussionmentioning
confidence: 99%
See 2 more Smart Citations